آداب الحوار وضوابطه من خلال القصص القرآني - Hameed,A.A.G. (Universiti Sains Islam Malaysia, 2024)
In the Quran, the art of dialogue is one of the most refined ways of human interaction. To know the right manners of dialogue for different occasions, we must refer to Quranic stories, which are based on the art of conversing. Hence, this paper aims to deduce the manners and restrictions of dialogue from these stories. After the introduction, the first section of this paper is on the manners if dialogue from Quranic stories including topics relating to speaking with manners and wisdom, sticking to the topic, refraining from extremism and indifference, and being honest, trustworthy and humble while listening to other people. The second section is on the restrictions of dialogue in Quranic stories, such as setting up an objective, being just in the face of allegation, accepting the possibility of the opponents righteousness in the presence of intellectual freedom, and avoiding over-reacting. This study finds that dialogue in the Quran addresses the difference for the sake of Allah. It also indicates the existing struggles between good and evil and its reflection on the lives of the prophets and those who preach for the sake of Allah.